The value of ammoniated hydrol in beef cattle wintering rations. - Richardson, D.; Baker, F.H.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Twenty Hereford heifer calves were divided as equally as possible on the basis of size, weight, and type into two lots of 10 animals each. Atlas sorghum silage was used as the roughage and the amount fed was adjusted to the amount the animals would clean up daily. The remainder of the ration was kept the same throughout the experiment. The ration at the beginning of the experiment is shown in Table 43. The concentrate part of the ration was mixed with the silage. A mineral mixture of two parts steamed bone meal and one part salt and salt alone were fed free choice. Water was available at all times.
Keywords: Beef; Ammoniated hydrol; Sorghum silage; Average daily gain